Well Water Testing and Understanding the Results - Farrell-Poe, Kitt (College of Agriculture and Life Sciences, University of Arizona (Tucson, AZ), 2011)
6 pp. === 1. Drinking Water Wells; 2. Private Water Well Components; 3. Do Deeper Wells Mean Better Water; 4. Maintaining Your Private Well Water System; 5. Private Well Protection; 6. Well Water Testing and Understanding the Results; 7. Obtaining a Water Sample for Bacterial Analysis; 8. Microorganisms in Private Water Wells; 9. Lead in Private Water Wells; 10. Nitrate in Private Water Wells; 11.Arsenic in Private Water Wells; 12. Matching Drinking Water Quality Problems to Treatment Methods; 13. Commonly Available Home Water Treatment Systems; 14. Hard Water: To Soften or Not to Soften; 15. Shock Chlorination of Private Water Wells === This fact sheet is one in a series of fifteen for private water well owners. The one- to four-page fact sheets will be assembled into a two-pocket folder entitled Private Well Owners Guide. The titles will also be a part of the Changing Rural Landscapes project whose goal is to educate exurban, small acreage residents. The authors have made every effort to align the fact sheets with the proposed Arizona Cooperative Extension booklet An Arizona Well Owners Guide to Water Sources, Quality, Sources, Testing, Treatment, and Well Maintenance by Artiola and Uhlman. The private well owner project was funded by both the University of Arizonas Water Sustainability Program-Technology and Research Initiative Fund and the USDA-CSREES Region 9 Water Quality Program.